PERLINDUNGAN KONSUMEN ATAS INFORMASI YANG TIDAK JELAS MENURUT UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Juni Desiani; N.G.N Renti Maharaini Kerti (Faculty of Law, Universitas Trisakti, 2023)
Starting with the owner of the food stall R.M., those who conduct their business activities with bad intentions can be identified by the lack of information in the form of transparent prices on the food menu. As a result, it has been discovered that business actors charge very high prices to customers who enter food stalls. How the Bogor City Regency regional regulations connect to the requirement for business actors to include pricing on the food menu list and what are the sanctions for food stall business actors R.M. are the formulations of the problem that the author explores. The research is descriptive and normative, use primary and secondary data, qualitative analysis, and deductive logic. The results of the research are the Consumer Protection Law protecting the rights of consumers for clear information.